Effects of Active Vitamin D or FGF23 Antibody on Hyp Mice Dentoalveolar Tissues. (December 2021) - Lira dos Santos, E.J.; Chavez, M.B.; Tan, M.H.; Mohamed, F.F.; Kolli, T.N.; Foster, B.L.; Liu, E.S.
Mutations in the PHEX gene lead to X-linked hypophosphatemia (XLH), a form of inherited rickets featuring elevated fibroblast growth factor 23 (FGF23), reduced 1, 25-dihydroxyvitamin D (1, 25D), and hypophosphatemia. Hyp mutant mice replicate the XLH phenotype, including dentin, alveolar bone, and cementum defects. We aimed to compare effects of 1, 25D versus FGF23-neutralizing antibody (FGF23Ab) monotherapies on Hyp mouse dentoalveolar mineralization. Male Hyp mice, either injected subcutaneously with daily 1, 25D or thrice weekly with FGF23 blocking antibody from 2 to 35 d postnatal, were compared to wild-type (WT) controls and untreated Hyp mice. Mandibles were analyzed by high-resolution micro–computed tomography (micro-CT), histology, and immunohistochemistry. Both interventions maintained normocalcemia, increased serum phosphate levels, and improved dentoalveolar mineralization in treated versus untreated Hyp mice. 1, 25D increased crown dentin volume and thickness and root dentin/cementum volume, whereas FGF23Ab effects were limited to crown dentin volume. 1, 25D increased bone volume fraction, bone mineral density, and tissue mineral density in Hyp mice, whereas FGF23Ab failed to significantly affect these alveolar bone parameters. Neither treatment fully attenuated dentin and bone defects to WT levels, and pulp volumes remained elevated regardless of treatment. Both treatments reduced predentin thickness and improved periodontal ligament organization, while 1, 25D promoted a more profound improvement in acellular cementum thickness. Altered cell densities and lacunocanalicular properties of alveolar and mandibular bone osteocytes and cementocytes in Hyp mice were partially corrected by either treatment. Neither treatment normalized the altered distributions of bone sialoprotein and osteopontin in Hyp mouse alveolar bone. Moderate improvements from both 1, 25D and FGF23Ab treatment regimens support further studies and collection of oral health data from subjects receiving a newly approved anti-FGF23 therapy. The inability of either treatment to fully correct Hyp mouse dentin and bone prompts further experiments into underlying pathological mechanisms to identify new therapeutic approaches.